Sedimentological characteristics of Alibonca Formation (Upper Oligocene-Lower Miocene) near Arapgir-Yoncalı area (Malatya) - Türkmen, Ibrahim; Taşgin, CalIbe Koç; Avşar, Niyazi; Aksoy, Ercan (Hacettepe Universitesi Yerbilmleri, 2011)
Tertiary units on the study area are Upper Oligocene-Lower Miocene Alibonca Formation and Burdigalian-Upper Miocene Malatya Volcanics. Alibonca Formation overlies unconformably Keban Metamorphics that is laterally and vertically associated with Malatya Volcanics. Twelve facies and three facies associations were identified in the Alibonca Formation. These facies are: horizontal bedded conglomerate, cross-bedded conglomerate, bedded sandstone, siltstone-fine grained sandstone, siltstone-claystone, organic-rich claystone, red mudstone, limestone, coal, algal packstone, bioclastic wackestone-packstone. These facies groups indicate alluvial fan, shallow lacustrine and carbonate shelf depositional environments.
Alibonca Formasyonu'nun (Üst Oligosen-Alt Miyosen) Sedimantolojik Özellikleri (Arapgir-Yoncalı-Malatya)
Keywords: Alluvial fan; Carbonate shelf; Coal; Malatya; Sedimentology; Shallow lacustrine